Rheo-Optical Shape Analysis of Human Blood Platelets - Affolter, Hubert; Pletscher, Alfred (Thrombosis and Haemostasis, 1982)
Alterations in rheo-optical signals obtained from suspensions of human blood platelets treated in various ways (drugs, storage in the cold, stirring, etc.) were monitored. A self-normalizing instrument measuring scattered light and relative amplitude of rapid oscillation of light intensity (noise level) at different angles was used. The following results have been obtained: 1. The light scattered at an angle of 40° was decreased with considerable selectivity by pseudopod formation, if aggregation was inhibited. 2. The noise levels at 0° and 40° were selectively diminished by the transition from the discoid to the spheroid shape of the platelets. 3. At 40°, but not at 0°, the noise level responded without delay and was not influenced by aggregate formation. Using this method alterations in platelet form, i.e. spheroid transformation and pseudopod formation, can be specifically and continuously monitored. In addition, the noise level at 40° is a definite quantitative measure of the discoid state. This allows the determination of platelet activation without manipulations such as changes in stirring rates or addition of drugs.
Keywords: Blood platelets; Shape change; Pseudopods; Light-scattering; Noise analysis